The Effect of mothers' education on under-five mortality from developing countries in South East Asia - HNIN THANT PHYU, Thant (KDI School, 2016)
This paper aims to contribute for the understanding of factors measuring mothers' educational levels on under-five children mortality from developing countries in South East Asia. Because extremely poverty remains a huge challenge in the South East Asia‟s developing countries. Set of factors related to socio-economic status on children survival. My study chose under-five mortality because it can influence infant and under-one mortality as well as Millennium Development Goals (MDG)'s indicator. My study of regression confirmed a strong association between mother‟s education and under-five child mortality and remained significant after control for other factors. The result imply that big part of the effect of mothers' education levels ( primary, secondary and tertiary) can be substituted by investing than other factors. Investment of girls' schooling is still one of the essential ways to contribute for child survival improvement in the long run because the findings of this research agree that “Mother is school”. On the other hand, the study of these areas will sustain the vital two sectors from policy makers. This paper was established that mothers‟ education has a negative impact on children mortality mostly; policy makers in region will have to focus their efforts on enhancing investment of education sector and reducing under-five child mortality by improving the performance of female education in these regions.
Thesis(Master) --KDI School:Master of Public Policy,2016